2006
DOI: 10.1111/j.1525-1314.2006.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

SHRIMP U‐Pb zircon dating from Sulu‐Dabie dolomitic marble, eastern China: constraints on prograde, ultrahigh‐pressure and retrograde metamorphic ages

Abstract: Laser Raman spectroscopy and cathodoluminescence (CL) images show that zircon from Sulu-Dabie dolomitic marbles is characterized by distinctive domains of inherited (detrital), prograde, ultrahighpressure (UHP) and retrograde metamorphic growths. The inherited zircon domains are darkluminescent in CL images and contain mineral inclusions of Qtz + Cal + Ap. The prograde metamorphic domains are white-luminescent in CL images and preserve a quartz eclogite facies assemblage of Qtz + Dol + Grt + Omp + Phe + Ap, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
133
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(144 citation statements)
references
References 84 publications
(236 reference statements)
9
133
1
1
Order By: Relevance
“…The process produced the blueschistfacies unit, the HP eclogite-facies unit, the UHP eclogitefacies unit, the low-amphibolite-and greenschist-facies unit in the Dabie Orogen Zheng et al, 2003;Xu et al, 2009;Li et al, 2009aLi et al, , 2010a. A considerable amount of geochronological data has confirmed that the deformation of the Qinling-Dabie Orogen happened in the Triassic-Early Jurassic times (244-180 Ma;Webb et al, 1999;Hacker et al, 1998Hacker et al, , 2000Hacker et al, , 2006Zhu et al, 2005;Liu et al, 2006aLiu et al, , 2006bZheng, 2008;Li et al, in press). The two sutures are obviously offset by the Tan-Lu Fault which is characterized by two-stages of sinistral strike slip movement (128-100 Ma and 161 Ma; Figures 1 and 2; Zhu et al, 2001Zhu et al, , 2005Wang, 2006).…”
Section: Geological Settingmentioning
confidence: 73%
“…The process produced the blueschistfacies unit, the HP eclogite-facies unit, the UHP eclogitefacies unit, the low-amphibolite-and greenschist-facies unit in the Dabie Orogen Zheng et al, 2003;Xu et al, 2009;Li et al, 2009aLi et al, , 2010a. A considerable amount of geochronological data has confirmed that the deformation of the Qinling-Dabie Orogen happened in the Triassic-Early Jurassic times (244-180 Ma;Webb et al, 1999;Hacker et al, 1998Hacker et al, , 2000Hacker et al, , 2006Zhu et al, 2005;Liu et al, 2006aLiu et al, , 2006bZheng, 2008;Li et al, in press). The two sutures are obviously offset by the Tan-Lu Fault which is characterized by two-stages of sinistral strike slip movement (128-100 Ma and 161 Ma; Figures 1 and 2; Zhu et al, 2001Zhu et al, , 2005Wang, 2006).…”
Section: Geological Settingmentioning
confidence: 73%
“…255 Ma as a result of continental subduction (Liu et al, 2008a), slightly earlier than the timing of peak UHP metamorphism in the Dabie-Sulu Orogen at ca. 240 Ma (Li et al, 2004;Liu et al, 2004bLiu et al, , 2006aLiu et al, , 2006bWan et al, 2005;Hacker et al, 2006;Wu et al, 2008). The 40 Ar/ 39 Ar age of ca.…”
Section: Timing Of Deformationmentioning
confidence: 98%
“…Two groups of zircon U-Pb ages of 245-240 Ma and 225-220 Ma are common for UHP metamorphic rocks from the central and southern Dabie orogen [46][47][48][49]. The former was generally interpreted as the age of metamorphic dehydration event occurring in the transition from HP to UHP conditions during continental subduction, and the latter as the age of metamorphic dehydration event in the transition from UHP to HP conditions during the exhumation of deeply subducted continental crust [42,50].…”
Section: Interpretation Of Diachroneity Along the Direction Of The Ormentioning
confidence: 99%